Monetary Policy and Financial Asset Prices: Empirical Evidence from Pakistan - Imran Umer Chhapra; Muhammad Usama Ali; Syeda Fizza Zehra; Falak Naz (Signifikan: Jurnal Ilmu Ekonomi, 2018)
Monetary transmission mechanism assumed to be significantly influenced by the effect of policy decisions on financial markets. However, various previous studies have come up with different outcomes. The purpose of this study is to examine the impact of monetary policy on different asset classes (shares and bonds) in Pakistan. This study using stock price and bond yield as dependent variable and discount rate, money supply, inflation, and exchange rate are independent variables. Data of all variables have collected from 2010 to 2016, and Vector Autoregressive (VAR) technique has applied. The empirical results indicate that there is an impact of monetary policy components on both stock and bond market as an increase in policy rate causes decline in stocks prices and bonds yields. The findings of this study will help the potential investors in making long-term (in general) and short-term (in particular) investment strategies concerning monetary policy.DOI: 10.15408/sjie.v7i2.7099